Identidade, diferenciação e metafísica de eventos - Morais, Eduardo José de Azevedo Charters Fuentes (2015)
The metaphysical discussion over causality and identity of events, in the aim of the physicalism, emerges in the context of the collapse of behaviorism. Whilst the paradigms of logical positivism dominated philosophy, the behaviorism dominated psychology. The rupture with the positivism was marked by the work of Willard V. O. Quine. The critics from the two dogmas of empiricism and the proposal of a radical translation allowed emergence of the theses of indetermination of meaning and inscrutability of reference. As alternative to empiricism, Quine recurs to ontological simplification and holism about theory, but considering the primacy of experience, he proposes a shift towards pragmatism. However, Quine’s pragmatism was founded in a behavioristic perspective on the acquisition of linguistic competences, and behaviorism didn’t stood as paradigm for the explanation of mentalist vocabulary. Quine had a great influence in the work and life of Donald Davidson. The ontological economy and the holism of theory marked Davidson’s work in his choice of events as basic entities and his approach to meaning in Truth and Meaning through a theory of truth. While in articles as Action, Reason and Causes Davidson develops an approach to the causal role of events in intention and action, stating that reasons are causes, in The Logical Form of Action Sentences and Causal Relations, he searches for the adequate logical forms of describing events and singular causal statements in order to establish an identity of events. The following metaphysical positions support, in Individuation of Events, a causal individuation criterion for events, and in Events as Particulars and Eternal vs Ephemeral Events, Davidson defends that events are spatiotemporal and unrepeatable particulars, finalizing a metaphysical discussion over of events that will enable him to approach the problem of the mind-body relation, in the anomalous monism argument. Donald Davidson’s anomalous monism presented in Mental Events proposes the thesis of monism – identity between physical events and mental events –, and anomalism of the mental – events do not fall under strict causal laws. To support these theses Davidson formulates three principles, whose conjunction gives us a non-reductionist version of token physicalism and, therefore, permits us to conciliate the mentalist vocabulary with the structure of physicalist language. In this sense, anomalous monism supports a supervenience theory of the mental. Despite the critics made to anomalous monism, as the epiphenomenalism accusation, the theory only crumbles in its initial presuppositions that is that of a priori causality and identity. Thus, the frailest aspects of the argument consist in the difficulty of tracking and identify in experience neural events with mental events, and in the formulation of strict laws. Those questions depend, respectively, on the advancement of neurosciences and physics. The present work, by the name of “Identity, Differentiation and Metaphysics of Events”, consists on an approach to metaphysics of events, in the context of the physicalism of tokens, more specifically to the Donald Davidson’s argument of the anomalous monism that argues for the identity of physical events and mental events and the causal role of mental events. It pretends, therefore, to coordinate the metaphysical discussion of events with Davidson’s anomalous monism.